Parasitism of cassava mealybug by Anagyrus lopezi: Effects of varying host and parasitoid densities - Muhammad Zainal Fanani; Aunu Rauf; Nina Maryana; Ali Nurmansyah; Dadan Hindayana (Society for Indonesian Biodiversity, 2020)
Abstract. Fanani MZ, Rauf A, Maryana N, Nurmansyah A, Hindayana D. 2020. Parasitism of cassava mealybug by Anagyrus lopezi: Effects of varying host and parasitoid densities. Biodiversitas 21: 4973-4980. The solitary endoparasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced into Indonesia in 2014 to control the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). The objectives of this study were to understand the influence of host and parasitoid densities on functional response and mutual interference of the parasitoid, by altering either the host or parasitoid density while keeping the other constant. The effects of host and parasitoid densities on parasitism, superparasitism, progeny production, and sex ratio were also assessed. Logistic regression was used to determine the shape of the functional response. Nonlinear least-squares regression was used to estimate the attack rate (a) and handling time (Th). Nicholson’s model and linear regression were used to determine per capita searching efficiency and interference coefficient, respectively. The logistic regression results suggested a Holling type II functional response to changing host densities, with an estimated attack rate (a) and handling time (Th) were 0.037 h-1 and 1.19 h, respectively. The estimated maximum number of mealybugs parasitized over 24-h period was 20.2 mealybugs. The wasp-mealybug ratio and offspring production increased significantly from 1:2 to 1:100 and from 1.35 to 10.45, respectively. However, the per capita number of parasitization decreased significantly from 14.20 to 4.37, with the increase in parasitoid density from 1 to 8. Searching efficiency of the parasitoid decreased significantly with increasing parasitoid density, with a mutual interference constant (m) of -0.52.